2016
DOI: 10.1007/s00415-016-8313-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting survival in ALS: a multicenter Italian study

Abstract: The aim of this multicenter, retrospective study is to investigate the role of clinical characteristics and therapeutic intervention on ALS prognosis. The study included patients diagnosed from January 1, 2009 to December 31, 2013 in 13 Italian referral centers for ALS located in 10 Italian regions. Caring neurologists collected a detailed phenotypic profile and follow-up data until death into an electronic database. One center collected also data from a population-based registry for ALS. 2648 incident cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 35 publications
12
68
0
1
Order By: Relevance
“…Age is a known risk factor for ALS. The majority of ALS patients have disease onset between 55 and 75 years of age, however patients with an age of onset <55 years and >75 years do exist and represent, respectively, the 22% and the 16% of all patients, as recently reported in a large multicenter Italian study (Calvo et al, 2016). Several factors, both genetic and environmental/exogenous, have been reported to modify age of onset in patients and animal models of ALS.…”
Section: Introductionmentioning
confidence: 85%
“…Age is a known risk factor for ALS. The majority of ALS patients have disease onset between 55 and 75 years of age, however patients with an age of onset <55 years and >75 years do exist and represent, respectively, the 22% and the 16% of all patients, as recently reported in a large multicenter Italian study (Calvo et al, 2016). Several factors, both genetic and environmental/exogenous, have been reported to modify age of onset in patients and animal models of ALS.…”
Section: Introductionmentioning
confidence: 85%
“…Most studies find that longer survival is associated with younger age at symptom onset, presentation with limb dysfunction rather than swallowing or speech disturbance, and specific forms of ALS such as symmetrical patterns (e.g. flail arm syndrome) or upper motor neuron predominant forms 50 . Conversely, cognitive impairment comprising executive dysfunction, rapid weight loss, and respiratory involvement at first examination, although not necessarily respiratory onset, predict a poor prognosis 5158 .…”
Section: Understanding Prognostic Factors In Alsmentioning
confidence: 99%
“…Among extensive epidemiological researches of ALS, an interesting and surprising observation is that ALS patients often encounter a loss of weight or a decrease of body mass index (BMI) at the early phase of diagnosis with many possible explanations [1, 13, 14, 15, 16, 17, 18, 19, 20]. Indeed, substantial change of BMI in ALS patients has been identified as an independent prognostic factor and has been linked to disease progression [13, 21, 22, 23, 24, 25, 26, 27]. For example, it is observed that a rapid reduction of BMI in ALS patients at the initial disease stage is a strong indicator of faster disease progression and shorter survival time; in contrast, nutritional intervention for ALS patients to increase BMI can prolong the survival time and leads to a delay in disease progression [28, 29, 30].…”
Section: Introductionmentioning
confidence: 99%